KONSEP WALKABILITY DALAM PENATAAN JALUR PEJALAN KAKI DI KAWASAN CBD BINTARO JAYA - Azzahra Ramadhani, Nadiva; Sasongko, Wisnu; Kurniawan, Eddi Basuki (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2023)
The Bintaro Jaya CBD area is located in South Tangerang City, Banten, which is dominated by land use trade and services. Walking has become a popular mode because of the distance between adjacent land uses, especially since the implementation of CFD in the Bintaro Jaya CBD area. However, there are problems with the infrastructure and facilities for pedestrian paths that are still uneven, so there is a need for an arrangement of pedestrian paths in the Bintaro Jaya CBD area. This study aims to determine the characteristics of the pedestrian path, determine the level of walkability, and select the direction of the arrangement of pedestrian paths based on the concept of walkability in the Bintato Jaya CBD area using the analysis method of pedestrian path characteristics, analysis of the level of pedestrian paths, priority analysis of lane arrangement criteria. Pedestrians using the Analytical Hierarchy Process (AHP) method, and analysis of the relationship between the results of the walkability level and the priority results of the pedestrian path arrangement criteria. The results of this study indicate that the lowest walkability score is in segment 3A with a value of 37.0 or not walkable and the walkability score for one area is 51.7 or waiting to walk. Based on the analysis of the results of the walkability level with the priority results of the pedestrian path arrangement criteria, segment 3A has a priority ranking of I or the first to be prioritized for the pedestrian path arrangement because it has a multiplication value of the total walkability value with the lowest weight of AHP results with a value of 20.13 and criteria infrastructure for the group with special needs has a priority ranking of I or the first to prioritize its arrangement because it has the lowest average score of 1.18.